Insights into the target-directed miRNA degradation mechanism in Drosophila ovarian cell culture. - Akulenko, N.; Mikhaleva, E.; Marfina, S.; Kutelev, I.; Kornyakov, D.; Bobrov, V.; Artamonov, A.; Arapidi, G.; Shender, V.; Ryazansky, S. (Biochimica et biophysica acta. Gene regulatory mechanisms., 2025)
Target-directed miRNA degradation (TDMD) is a process of post-transcriptional regulation of miRNA stability in animals induced by an extended pairing of Ago-bound miRNAs with specialized complementary RNA targets. As suggested by studies on human cell culture, Ago engaged with the extended duplex is recognized by the ZSWIM8 receptor of the Cullin-RING-ligase complex (CRL3), which also contains Cul3, EloB, and EloC proteins. The CRL activity is accelerated by the neddylation of Cul3 with the involvement of the E2 conjugating protein UbcE2M. The CRL ubiquitinates Ago, resulting in proteolysis of Ago and degradation of the released miRNAs. To date, the molecular mechanism of TDMD has not been studied in other species. To further characterize TDMD in animals, we investigated the protein Dora, the Drosophila ortholog of ZSWIM8, in the culture of Drosophila ovarian somatic cells (OSC). We showed that Dora in OSCs localizes in protein granules unrelated to P- and GW-bodies. The dora knockout resulted in the accumulation of multiple miRNAs, including miR-7-5p, and transcriptome-wide affected the mRNA targets of differentially expressed miRNAs. We also showed that Dora associates with proteins of the CRL3 complex, and the depletion of CRL3 components or inhibition of Cul3 neddylation upregulates miR-7-5p. We concluded that the molecular mechanism of TDMD is conserved in humans and Drosophila. Finally, we found that cells without Dora have an impaired Notch signaling pathway, indicating that TDMD in OSCs may contribute to the modulation of the Notch pathway.